Modi's 'Make in India' Industrial Reform Policy and East Asian Flying-Geese Paradigm - Chang Woon Nam; Sumin Nam; Peter Steinhoff (Center for Economic Studies and ifo Institute (CESifo), 2017)
The on-going `Make in India' campaign aims at manufacturing revival. Its characteristics resemble East Asian industrial reform and growth policies based on the flying-geese model which highlights `step-by-step' changes in a country's specialisation pattern and global competitiveness accompanied by economic growth. Unlikely, `Make in India' comprises heterogeneous measures `simultaneously' supporting industries in different development stages from labour and capital-intensive to high-tech industries and modern services. Moreover issues like world-market uncertainty discouraging export activities; poverty-reduction-oriented labour-industry promotion vs overall productivity increase; and complementary role of IT services for industrial modernisation and growth, will shape the success of India's diversified industrial policy.
Keywords: O10; O40; O50; L60; 330; development stage theory; flying-geese paradigm; industrial growth and specialisation; Make in India; East Asia; international comparison